Effects of by-products as cement replacement materials towards concrete carbonation depth - Muhammad Hariz, Mohamed Idris (2013)
Carbonation is a common threat to reinforced concrete structures. Carbonation causes deterioration by the corrosion of the reinforcement bars as it allows moisture to penetrate to the depth of the steel and also leads to concrete spalling. Althoughthe causes; mechanisms and factors that promote concrete carbonation have been widely studied, there is.verylittle data relating carbonation with industrial by-products -such as palm oil fuel ash(POFA), pulverized fly ash (PFA) and whatsoever. Thus, the aim of this research is to study the effects of POFA and PFA towards concrete carbonation depth as POFA and PFA have been used extensively as cement replacement materials to improve concrete characteristics. Three different samples at 3 years of age were used, each for control concrete, POFA concrete and PFA concrete where POFA and PFA are added up to 30% cement replacement, starting with 10% and 20%. Water absorption test, alkalinity test and carbonation test were all carried out to achieve the objectives of this research. From the results, reduction of alkalinity and permeability occurs in concrete containing POFA and PFA and is decreasing as the amount of POFA and PFA is increased. Though permeability of concrete is improved due to introduction of POFA and PFA, carbonation depth is found to be higher in those concrete compared to control concrete.